2005
DOI: 10.1097/01.phm.0000163862.89217.fe
|View full text |Cite
|
Sign up to set email alerts
|

Two Exercise Interventions for the Management of Patients with Ankylosing Spondylitis

Abstract: The experimental protocol developed by our research group, based on the GPR method and specific strengthening and flexibility exercises of the muscle chains, offers promising results in the management of patients suffering from AS. Further trials on this topic are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
1
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 17 publications
6
94
1
16
Order By: Relevance
“…Vesovic-Potic et al [25] reported significant correlation between disease duration, symptoms duration and BASFI. The efficacy of various physiotherapy programs has been assessed by several groups [12,14,15,[26][27][28] concluding that exercise programs are important and useful part of the complex therapy of ASDagfinrud et al [14] recently reviewed the available body of evidence on the efficacy of physiotherapy interventions in AS. This meta-analysis suggests that an individual homebased or supervised exercise program is better than having no intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesovic-Potic et al [25] reported significant correlation between disease duration, symptoms duration and BASFI. The efficacy of various physiotherapy programs has been assessed by several groups [12,14,15,[26][27][28] concluding that exercise programs are important and useful part of the complex therapy of ASDagfinrud et al [14] recently reviewed the available body of evidence on the efficacy of physiotherapy interventions in AS. This meta-analysis suggests that an individual homebased or supervised exercise program is better than having no intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In the randomized controlled trial by Fernandez-de-las-Penas et al [26] a conventional physiotherapeutic intervention (20 spinal and chest exercises and stretching of the shortened muscles) and their own protocol (based on the postural affectation of the AS, the shortened muscles were treated by stretching during 4 months) were compared. Both groups showed an improvement in all mobility measures, as well as in BASFI and BASDAI, but their own protocol showed a better improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos controlados e randomizados demonstraram eficácia no tratamento da espondilite anquilosante, a partir de um tratamento de reeducação postural global em longo prazo (15)(16)18). Fernández-de-las-Peñas et al (15) trataram pacientes com espondilite anquilosante durante quatro meses e observaram melhora da mobilidade do esqueleto axial após a realização da técnica de RPG, utilizando medidas de mobilidade do Bath Ankylosing Spondylitis Disease Metrology Index (BASMI) e Bath Ankylosing Spondylitis Functional Index (BASFI).…”
Section: Discussionunclassified
“…O alinhamento horizontal do piso, do tripé e da máquina foi aferido com um nível de madeira (6). Embora a técnica seja muito difundida em paí-ses, como Brasil, França, Itália e Espanha, e diversos fisioterapeutas utilizarem a técnica com resultados empíricos (14), poucos estudos são encontrados sobre a técnica de RPG (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Métodosunclassified
See 1 more Smart Citation